Rent Seeking in Power and Energy Sector in Bangladesh - Sultana, Moshahida (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
As the power and energy sector of Bangladesh has become increasingly susceptible to external shocks like Ukraine war and dollar crisis, the growing dependency on imported energy is being questioned from the energy security point of view. While the technology and policy actors hold depletion of gas resources and the need for diversification as the reasons to justify increasing import dependency, the proponents for energy security using indigenous resources point out at the negligence in exploring potential indigenous gas reserve and the inability to deploy renewable energy. Why in last one-decade Bangladesh adopted new energies like coal, nuclear, and LNG, rather than exploring natural gas and incentivizing solar and wind, has still remained a puzzle. This paper uses the rent seeking framework to identify how rent seeking structures differ across energy technologies and whether the differences had any implications for incentivizing some energy use while not incentivizing others. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 263-286